2017
DOI: 10.1007/s10872-017-0453-x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between salinity in the northwestern Bering Sea, the Bering Strait throughflow and sea surface height in the Arctic Ocean

Abstract: The correlation between transport via the Bering Strait throughflow (BTF) and sea surface salinity (SSS) in the Bering Sea has been examined mainly using an atmosphere-ocean-ice coupled climate model that has an eddy-permitting ocean component. The SSS anomaly in the northwestern Bering Sea is high from winter to spring when the BTF transport anomaly is large in the cold season. Similar features can be seen in an observation dataset and two kinds of ocean data assimilation product. BTF transport is strongly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…More recently, using a conceptual model, Danielson et al (2014) correlated wind, pressure, and sea surface height north and south of the strait with the throughflow and suggested that the Bering shelf circulation is highly controlled by basin-scale wind patterns, particularly the Aleutian Low in the Bering Sea/Gulf of Alaska, with additional contributions from the Beaufort 10.1029/2020JC016213 and Siberian Highs and modifications from coastal shelf waves. Kawai et al (2018) also find relationships between model sea surface heights in the northeast Bering Sea and the southwest Chukchi Sea with the flow through the Bering Strait. Yet more recent work (Peralta-Ferriz & Woodgate, 2017) finds high correlations (correlation coefficient ∼ 0.6) between monthly flow variability and a specific pattern of ocean bottom pressure (OBP), namely, a pattern dominated by low OBP in the East Siberian Sea (assisted in winter by high OBP over the Bering Sea Shelf).…”
Section: Introductionmentioning
confidence: 66%
“…More recently, using a conceptual model, Danielson et al (2014) correlated wind, pressure, and sea surface height north and south of the strait with the throughflow and suggested that the Bering shelf circulation is highly controlled by basin-scale wind patterns, particularly the Aleutian Low in the Bering Sea/Gulf of Alaska, with additional contributions from the Beaufort 10.1029/2020JC016213 and Siberian Highs and modifications from coastal shelf waves. Kawai et al (2018) also find relationships between model sea surface heights in the northeast Bering Sea and the southwest Chukchi Sea with the flow through the Bering Strait. Yet more recent work (Peralta-Ferriz & Woodgate, 2017) finds high correlations (correlation coefficient ∼ 0.6) between monthly flow variability and a specific pattern of ocean bottom pressure (OBP), namely, a pattern dominated by low OBP in the East Siberian Sea (assisted in winter by high OBP over the Bering Sea Shelf).…”
Section: Introductionmentioning
confidence: 66%
“…The Arctic's surface waters are influenced by complex atmospheric and oceanic interactions, of which the cryosphere plays an important role. Differences in SST, SSS, and SIC provide valuable insight into trends of Arctic FW flux and its connection to lower latitudes [56] (Figure 2). The warm inflow of water in the Atlantic region restricts the extent of sea ice formation as seen in Figure 2a,b.…”
Section: Arctic's Mean State (2016-2018)mentioning
confidence: 99%
“…As the wintertime oceanic mixed layer reaches the bottom in the shallow continental shelf region (Kawai et al, 2018), the mixed layer in the shelf region is cooled more than that in the deep southwestern basin. In the Bering Sea, the bottom topography regulates the upper ocean temperature and the low-level atmosphere, as Xie et al (2002) indicated for the Yellow and East China Seas.…”
Section: Effect On Shortwave Radiation and Precipitation Into The Oceanmentioning
confidence: 99%